Identification of O-glycosylated proteins that are aberrantly excreted in the urine of patients with early stage ovarian cancer - Wai Mu, A.K.; Lim, B.K.; Hashim, Onn Haji; Shuib, Adawiyah Suriza (2013)
Cancer is known to induce or alter the O-glycosylation of selective proteins that may eventually be excreted in the patients’ urine. The present study was performed to identify O-glycosylated proteins that are aberrantly excreted in the urine of patients with early stage ovarian cancer (OCa). These urinary glycoproteins are potential biomarkers for early detection of OCa. In this study, urinary proteins of patients with early stage OCa and age-matched OCa negative women were subjected to two-dimensional gel electrophoresis and detection using a lectin that binds to the O-glycosylated proteins. Our analysis demonstrated significant enhanced expression of clusterin and leucine-rich alpha-2-glycoprotein, but lower levels of kininogen in the urine of the OCa patients compared to the controls. The different altered levels of these urinary glycoproteins were further confirmed using competitive ELISA. Our data are suggestive of the potential use of the aberrantly excreted urinary O-glycosylated proteins as biomarkers for the early detection of OCa, although this requires further validation in a large clinically representative population.